LAYANAN RESPONSIF MELALUI TEKNIK KONSELING REALITAS DALAM MENGATASI KORBAN LOVE SCAMMING DI SMA NEGERI 1 DAYEUHKOLOT - Amin, Guruh Almuslihun; Arifin, Isep Zaenal; Fajar, Dadang Ahmad (PABKI (Perkumpulan Ahli Bimbingan dan Konseling Islam) Indonesia, 2025)
The phenomenon of love scamming among adolescents is increasingly concerning, particularly at SMA Negeri 1 Dayeuhkolot where students are active social media users. This scheme exploits romantic relationships to deceive victims emotionally and financially, affecting their psychological, social, and academic conditions. The objective is to describe the victims’ behaviors, identify the causal factors, and explain both the process and results of victim management using responsive services based on reality counseling. The theoretical framework refers to Glasser’s Reality Counseling, which emphasizes personal responsibility, awareness of choices, and rational decision-making in behavioral change. This research employs a qualitative approach with a descriptive method. Primary data were obtained through in-depth interviews, observations, and document studies involving victims, peers, guidance and counseling teachers, homeroom teachers, and the vice principal for student affairs. Secondary data were collected from school documents, social media, academic literature, and records of similar cases. Data analysis involved reduction, categorization, presentation, and conclusion drawing. The findings reveal that victims experienced deep sadness, panic attacks, social withdrawal, and fear of social media notifications due to threats of personal data exposure. Contributing factors include individual aspects (poor self-control, emotional immaturity), family (lack of communication, weak supervision), school (academic pressure, negative peer interactions), social (peer influence, unhealthy media exposure), and cultural elements. Responsive services included summoning the victim, exploring the chronology, providing reality counseling, and following up on emotional recovery. The application of reality counseling proved effective, as indicated by improved communication with family, increased social interaction, cessation of perpetrator intimidation, and the victim’s renewed focus on the future without prolonged trauma. In conclusion, responsive services based on reality counseling can restore victims’ emotional and social conditions and serve as a preventive strategy against similar cases in schools.